Songs as a Medium for Reflecting Cross-Cultural Tensions: An Analysis of the Lyrics of the Song 'Mangu' in the Context of Indonesian Diversity: Penelitian - Putra Darma, Virga; Bernadeta, Anggis; Robbani, Nadzira (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the song Mangu by Fourtwnty as a symbolic medium that reflects the tension in interfaith and cultural relations in Indonesia. Using a qualitative approach and narrative method, this study examines the relationship between song lyrics and the personal experience of an informant named Marhamah Khoirunnisa, who is in a relationship with a couple of different faiths and cultures. The findings show that Mangu's song is not only an expression of personal grief, but also contains a collective narrative of love that is hindered by religious boundaries, family pressure, and established social norms. Lyrics like "you there, I'm across from you" contain symbolic meanings that reflect emotional and structural distances that are difficult to bridge. This song proves to be a means of emotional catharsis and identity negotiation for individuals who are at the intersection of love and trust. Thus, Mangu is positioned as a cultural text that plays a role in representing the complexity of Indonesia's diversity through the medium of music.